1996
DOI: 10.1071/ch9961325
|View full text |Cite
|
Sign up to set email alerts
|

New Antibiotic Uperin Peptides From the Dorsal Glands of the Australian Toadlet Uperoleia mjobergii

Abstract: The dorsal glandular extract of the toadlet Uperoleia mjobergii contains more than 20 peptides. We report the amino acid sequences of the seven major peptides: these were determined by a combination of mass spectrometry and automated Edman sequencing. Three of these peptides have 19 amino acid residues and belong to the uperin 2 group of peptides [e.g. uperin 2.6, Gly Ile Leu Asp Ile Ala Lys Lys Leu Val Gly Gly Ile Arg Asn Val Leu Gly Ile (OH)], while the other four have 17 residue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 0 publications
2
50
0
Order By: Relevance
“…To mimic the zwitterionic nature of peptides at physiological pH (7.4), a charge of +1 and −1 is usually assigned to the first and last backbone atoms of the peptide that is, the N‐ and C‐terminus, respectively. However, in this case, the wild‐type uperin 3.5 is amidated at the C‐terminus, which means that no charge was assigned to the backbone atom at the C‐terminus. Both FA and CG MD were used for simulating the following systems, (a) two uperin 3.5 peptides in a periodic box, and (c) 20 uperin 3.5 peptides in a periodic box, details of which are provided in Table .…”
Section: Methodsmentioning
confidence: 94%
See 1 more Smart Citation
“…To mimic the zwitterionic nature of peptides at physiological pH (7.4), a charge of +1 and −1 is usually assigned to the first and last backbone atoms of the peptide that is, the N‐ and C‐terminus, respectively. However, in this case, the wild‐type uperin 3.5 is amidated at the C‐terminus, which means that no charge was assigned to the backbone atom at the C‐terminus. Both FA and CG MD were used for simulating the following systems, (a) two uperin 3.5 peptides in a periodic box, and (c) 20 uperin 3.5 peptides in a periodic box, details of which are provided in Table .…”
Section: Methodsmentioning
confidence: 94%
“…An increasing number of anti‐microbial peptides (AMPs) have been identified with an inherent ability to form amyloid structures . Uperin 3.5 (GVGDL 5 IRKAV 10 SVIKN 15 IV‐NH 2 ) is one such broad‐spectrum AMP obtained from the skin secretion of the toadlet Uperoleia mjobergii . Uperin 3.5 is unusual, as it does not aggregate in pure water, but self‐aggregates in saline buffer at neutral pH to form amyloid fibrils .…”
Section: Introductionmentioning
confidence: 99%
“…5). A family of structurally related peptides, termed the uperins, has been isolated from the Australian frogs Uperoleia mjoberii [51] and Uperoleia inundata [52] that are active against Gram-positive bacteria. From the species Crinia signifera, two peptides differing by a single amino acid, termed signiferin 2.1 and signiferin 2.2, were identified that are also active against Gram-positive bacteria [53].…”
Section: Myobatrachidaementioning
confidence: 99%
“…Uperin 3.5 (U3.5, GVGD 5 LIRKA 10 VSVIK 15 NIV‐NH 2 , Figure ) from the toadlet Uperoleia mjobergii is a remarkable AMP that aggregates into amyloid fibrils when dissolved in phosphate buffer at neutral pH . All the uperin peptides tested to date exhibit antimicrobial activity toward a wide range of Gram‐positive bacteria, with U3.5 having the highest propensity for aggregation . As a result, it is an ideal candidate to study both antimicrobial and amyloidogenic mechanisms and the potential association between these two properties.…”
Section: Introductionmentioning
confidence: 99%